CORRELATION OF STUDENTS' WELL-BEING AND PROBLEM-SOLVING SKILLS IN MATHEMATICS - Naila Amalia; Siti Hajar Mauluddina; Kei Hanakasi; Wahyunengsih (Universitas Nias Raya, 2025)
This literature review examines the relationship between student well-being and mathematical problem-solving skills, drawing on both global and Indonesian studies. Using Polya's problem-solving framework, Fredrickson's broaden-and-build theory, and SciSpace-assisted thematic analysis, the study synthesizes its findings. Results show significant correlations, notably between resilience and problem-solving ability (R = 0.819), with emotionally stable students demonstrating better cognitive flexibility and strategic adaptation. Three key mediators were identified: social support (especially in collectivist cultures), self-efficacy, and classroom emotional climate. Indonesian-specific findings reveal that academic pressure intensifies anxiety's negative impact on non-routine problem-solving. This review proposes three actionable recommendations: (1) teacher training in emotion-responsive pedagogy, (2) integration of metacognitive and coping strategies, and (3) school-based well-being interventions. Limitations include the dominance of correlational studies and limited socioeconomic factor consideration. Future research is encouraged to apply longitudinal designs and culturally adapted measurement tools to understand the dynamic between emotional states and problem-solving in education.